Monounsaturated and Saturated, but Not n-6 Polyunsaturated Fatty Acids Decrease Cartilage Destruction under Inflammatory Conditions: A Preliminary Study. (October 2013) - Bastiaansen-Jenniskens, Y.M.; Siawash, M.; van de Lest, C.H.A.; Verhaar, J.A.N.; Kloppenburg, M.; Zuurmond, A.-M.; Stojanovic-Susulic, V.; Van Osch, G.J.V.M.; Clockaerts, S.
Purpose: Osteoarthritis (OA) is associated with obesity in which altered fatty acid levels have been observed. We investigated whether the most common fatty acids in synovial fluid influence cartilage deterioration in OA. Design: Cartilage was obtained from OA patients undergoing total knee arthroplasty. Chondrocytes or cartilage explants were cultured with linoleic (n-6 polyunsaturated), oleic (monounsaturated), or palmitic (saturated) acid. After preculture, media were renewed and inflammation was simulated in half of the samples by addition of 10 ng/mL tumor necrosis factor-α (TNFα) with or without the fatty acids. Effects on lipid uptake (Oil-Red-O), cell toxicity (lactate dehydrogenase), prostaglandin-E2 (PGE2) release and gene expression for prostaglandin-endoperoxide synthase-2 (PTGS2), matrix metalloproteinase-1 (MMP1), and MMP13, and a disintegrin and metalloproteinase with thrombospondin motifs 4 were determined on chondrocytes in monolayer. Effects on glycosaminoglycan (GAG) release were evaluated on cartilage explants. Results: None of the fatty acids were cytotoxic and all were taken up by the cells, resulting in a higher amount of intracellular lipid in chondrocytes. Linoleic acid increased PGE2 production in the presence of TNFα. Oleic acid and palmitic acid inhibited MMP1 gene expression in chondrocytes stimulated with TNFα. In cartilage explants, GAG release was also inhibited by oleic acid and palmitic acid, and oleic acid decreased PTGS2 gene expression in stimulated chondrocytes. Conclusions: Linoleic acid has a pro-inflammatory effect on cartilage whereas oleic acid and palmitic acid seem to inhibit cartilage destruction. These results indicate that altered fatty acid levels may influence loss of cartilage structure in OA.